(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Inflammation of bone is called as Osteomyelitis. Osteomyelitis of calcaneum is a condition progressive towards morbidity of the patient because of the chronicity and severe complication. According to modern science, available treatment on calcaneum osteomyelitis is debridement, incision and drainage. But due to chronicity of disease there may be relapse of the infection. According to Ayurved Science, this condition can be correlated with Antarvidradhi and was treated according to its principles like Snehana, Mruduswedana, Raktprasadkar, Dhatubalaya rasayan. Methodology: A patient of 47 year old visited SHREE Ayurvedic Chikitsalaya on 28.10.2019, with severe pain in right foot, edema all over the foot and patient with complete inability to walk and stand. This condition was diagnosed as Antarvidradhi. In this condition, following internal medicines were given to the patients for 2 months like Varandi kashayam, Phaltrikadi Kashyam, Chaturmukh rasa, Vasant kusumakar rasa, Kaishor Guggul. Along with this, externally lepa of Mahasneham and cooked mamsa of goat was also applied for 2 months. Results: After using this treatment, significant results were observed in the form of reduced signs and symptoms like edema, pain, difficulty in walking that were complained in the first visit to the OPD. And there is also increased stamina & confidence while walking. Conclusion: Considering the above observation in the patient, given treatment is useful in reducing signs like edema, pain and difficulty in walking. Hence it can be concluded that it is useful in Osteomyelitis of calcaneum i.e. Antarvidradhi.